Exploring the Roots of Political Dynasties from the Perspective of the Democratic System: Legal and Political Reform as a Balance in Election Contestation - Antony; Lie, Cindy; Shanylla, Joen (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2024)
Political dynasties are not a new phenomenon, but an old phenomenon that continues to grow from year to year in Indonesia's democratic government system to date. one of the causes of Indonesia's political dynasties is that political reform moves very fast like a meteor but on the contrary, legal reform is very slow like a snail. This research aims to explore the roots of political dynasties in the perspective of the democratic system, especially in the state and can contribute as a basis for thought and strategy in preventing political dynasties, especially in democracies that experience election dynamics. This research uses socio-legal research methods. The results of this study found that the phenomenon of political dynasties has grown rapidly in Indonesia's political system, but political dynasties cannot be prohibited because it is the constitutional right of everyone, but political dynasties can be inhibited and prevented by conducting legal reform and political reform in balance. In addition to reforming, the use of Pancasila ideology also increases awareness and nationalism, especially in responding to the problems of political dynasties that occur in society.